Hydrophobic nature of rat lymph chylomicrons - Güldür, T; Karabulut, AB; Bayraktar, N; Kaynar, Ö (Elsevier, 2004)
Background: A typical molecular structure of a lipoprotein is composed of hydrophobic lipids at the core and hydrophilic apolipoprotein side chains and lipid head groups at the surface. Some of the hydrophobic characteristics of rat lymph chylomicrons were investigated. Methods: Thoracic duct was cannulated and lymph was collected overnight. Chylomicrons (>100 rim) were isolated by ultracentrifugation at 4 x 10(6) x g min. Since particle aggregation is a characteristic of hydrophobic nature of lipoproteins, as an index of aggregation, the turbidity generated by vortexing and storage of chylomicrons was measured spectrophotometrically at 680 nm. We also assessed the ability of chylomicrons to interact with five different hydrophobic interaction chromatography (HIC) media. Results: Neither shaking nor prolonged storage at 4 degreesC produced an increase in the optical density of chylomicron solution indicating no aggregation took place. Typical elution profiles of chylomicrons through octyl, phenyl (high substance) and butyl sepharose columns showed two peaks. Peak I material emerged with 4 mol/l NaCl in a position corresponding to the void volume and peak II material eluted with water. Phenyl sepharose (high performance) media exhibited the maximum binding strength towards chylomicrons among the five different media. In the case of pheryl sepharose (low substance) column, an additional material was eluted with 3 mol/l NaCl between peaks I and II. These results indicate the heterogeneity of chylomicron surface hydrophobicity. Conclusion: Since particle aggregation is a characteristics of hydrophobicity of lipoproteins and believed to be an underlying cause of atherosclerosis, fractionation of lipoproteins by hydrophobic interaction chromatography may introduce a new approach into the assessment of lipoprotein atherogeneicity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: aggregation; chylomicron; hydrophobicity; atherosclerosis; chromatography